2005
DOI: 10.1177/107906320501700306
|View full text |Cite
|
Sign up to set email alerts
|

Violent Juvenile Sex Offenders Compared with Violent Juvenile Nonsex Offenders: Explorative Findings From the Pittsburgh Youth Study

Abstract: Only a limited number of studies have compared the psychosocial characteristicsSince the recognition in the 1970's and 1980's that juveniles are capable of committing sex offenses, many studies have investigated this problem. However, many methodological shortcomings were inherent to these studies, including small sample size, biased sampling, nonstandardized instruments and a reliance on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 43 publications
5
60
0
1
Order By: Relevance
“…Thus the JSO-H+ group in the present study showed a versatile, antisocial profile which has been often described in former studies of JSO (Butler & Seto, 2002;Freeman et al, 2005;Ronis & Borduin, 2007;Seto & Barbaree, 1997;van Wijk, Loeber et al, 2005;van Wijk, van Horn, Bullens, Bijleveld, & Doreleijers, 2005;van Wijk et al, 2006). Sexual inadequate behavior of these JSO represents a part of a more comprehensive behavioral problem which also includes general rule breaking behaviors and social deficits.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Thus the JSO-H+ group in the present study showed a versatile, antisocial profile which has been often described in former studies of JSO (Butler & Seto, 2002;Freeman et al, 2005;Ronis & Borduin, 2007;Seto & Barbaree, 1997;van Wijk, Loeber et al, 2005;van Wijk, van Horn, Bullens, Bijleveld, & Doreleijers, 2005;van Wijk et al, 2006). Sexual inadequate behavior of these JSO represents a part of a more comprehensive behavioral problem which also includes general rule breaking behaviors and social deficits.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, some studies found that JSO did not differ from violent or general juvenile offenders according to their early childhood problems, current behavioral adjustment, personality traits, antisocial attitudes and family background characteristics (Butler & Seto, 2002;Freeman et al, 2005;Ronis & Borduin, 2007;van Wijk, Loeber et al, 2005). Because of these findings, some authors concluded that JSO do not need specialized sexual treatment and may profit from intensive family and social interventions as general antisocial youth do (Letourneau et al, 2009;Ronis & Borduin, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is not the norm according to the literature [4] [13] [26] [27]. This result could be caused by using interview as the main method for gathering information, use of self-protective mechanisms in the interview situation and retention of information.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 75%
“…Some studies have indicated that the same risk factors are found among sexual offenders and non-sexual offenders: poor attachment to family and school, poorer attachment between parent and adolescent, and lower parental involvement [26] [27], although a recent meta-analysis could not find support for these factors as related to adolescent sexual offending [28]. A study of 4000 Swedish and Norwegian male high school students found that young people who had experienced sexual coercion were approximately three times more likely to engage in sexually coercive behaviour than those without such experiences [28].…”
Section: Introductionmentioning
confidence: 99%